Rút gọn \(A=\frac{a^6-2a^5+a-2}{a^5+a}\)\(\left(a\ne-1\right)\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(2\sqrt{3a}-\sqrt{75a}+a\sqrt{\frac{6}{5}.\frac{5}{2a}}-\frac{2}{5}\sqrt{300a^3}\)
\(=2\sqrt{3a}-5\sqrt{3a}+a\sqrt{\frac{3}{2}}-\frac{2}{5}.10.a\sqrt{3a}\)
\(=-3\sqrt{3a}+\sqrt{\frac{3}{a}.a^2-4\sqrt{3a}}\)
\(=-3\sqrt{3a}+\sqrt{3a}-4a\sqrt{3a}\)
\(=-2\sqrt{3a}-4a\sqrt{3a}\)
\(=-2\sqrt{3a}\left(1+2a\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(=\left[\dfrac{\left(a-1\right)^2}{a^2+a+1}+\dfrac{2a^2-4a-1}{\left(a-1\right)\left(a^2+a+1\right)}+\dfrac{1}{a-1}\right]:\dfrac{2a}{3}\)
\(=\dfrac{a^3-3a^2+3a-1+2a^2-4a-1+a^2+a+1}{\left(a-1\right)\left(a^2+a+1\right)}\cdot\dfrac{3}{2a}\)
\(=\dfrac{a^3-1}{\left(a-1\right)\left(a^2+a+1\right)}\cdot\dfrac{3}{2a}=\dfrac{3}{2a}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(B=\left(\dfrac{2}{a^2+a}-\dfrac{2}{a+1}\right):\dfrac{1-a}{a^2+2a+1}\)
\(=\left(\dfrac{2}{a\left(a+1\right)}-\dfrac{2a}{a\left(a+1\right)}\right):\dfrac{1-a}{\left(a+1\right)^2}\)
\(=\dfrac{2\left(1-a\right)}{a\left(a+1\right)}\cdot\dfrac{\left(a+1\right)^2}{1-a}\)
\(=\dfrac{2a+2}{a}\)
Sai đề phải k bạn